2005
DOI: 10.1080/02533839.2005.9671054
|View full text |Cite
|
Sign up to set email alerts
|

Stress analysis of locking screws for femoral antegrade and retrograde nailing constructs

Abstract: Based on elastic beam-column theory, antegrade and retrograde femur-nail-screw constructs were modeled to perform stress analysis on the locking screws. The effects of the nail-cortical and nail-subchondral support, the geometrical properties of the femur-nail-screw construct, and the nailing types on the locking screw stress were evaluated. The cortex that contacts the nail was simulated as a linearly elastic quasifoundation to support the medially deflected nail. The contact reaction of the femoral subchondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…The use of fully threaded, cortical screws to lock intramedullary nails was first documented in 1990 when biomechanical testing showed that its mechanical strength allowed loading up to 4500 N [10]. In an intramedullary nail, the interlocking screws serve as load-bearing constructs whose breaking point is directly proportional to its cortical contact, length, and core diameter [3,4]. To avoid stress risers, the screw length must maximize cortical contact and its diameter must be less than 50% of the nail diameter -both criteria satisfied by fully threaded, cortical screws [10].…”
Section: Discussionmentioning
confidence: 99%
“…The use of fully threaded, cortical screws to lock intramedullary nails was first documented in 1990 when biomechanical testing showed that its mechanical strength allowed loading up to 4500 N [10]. In an intramedullary nail, the interlocking screws serve as load-bearing constructs whose breaking point is directly proportional to its cortical contact, length, and core diameter [3,4]. To avoid stress risers, the screw length must maximize cortical contact and its diameter must be less than 50% of the nail diameter -both criteria satisfied by fully threaded, cortical screws [10].…”
Section: Discussionmentioning
confidence: 99%